Visceral adipose tissue and leptin increase colonic epithelial tight junction permeability via a RhoA‐ROCK‐dependent pathway. Issue 3 (15th November 2013) - Le Dréan, Gwenola; Haure‐Mirande, Vianney; Ferrier, Laurent; Bonnet, Christian; Hulin, Philippe; de Coppet, Pierre; Segain, Jean‐Pierre
Abstract : Proinflammatory cytokines produced by immune cells play a central role in the increased intestinal epithelial permeability during inflammation. Expansion of visceral adipose tissue (VAT) is currently considered a consequence of intestinal inflammation. Whether VAT per se plays a role in early modifications of intestinal barrier remains unknown. The aim of this study was to demonstrate the direct role of adipocytes in regulating paracellular permeability of colonic epithelial cells (CECs). We show in adult rats born with intrauterine growth retardation, a model of VAT hypertrophy, and in rats with VAT graft on the colon, that colonic permeability was increased without any inflammation. This effect was associated with altered expression of tight junction (TJ) proteins occludin and ZO‐1. In coculture experiments, adipocytes decreased transepithelial resistance (TER) of Caco‐2 CECs and induced a disorganization of ZO‐1 on TJs. Intraperitoneal administration of leptin to lean rats increased colonic epithelial permeability and altered ZO‐1 expression and organization. Treatment of HT29‐19A CECs with leptin, but not adiponectin, dose‐dependently decreased TER and altered TJ and F‐actin cytoskeleton organization through a RhoA‐ROCK‐dependent pathway. Our data show that adipocytes and leptin directly alter TJ function in CECs and suggest that VAT could impair colonic epithelial barrier.—Le Dréan, G., Haure‐Mirande, V., Ferrier, L., Bonnet, C., Hulin, P., de Coppet, P., Segain, J.‐P. Visceral adipose tissue and leptin increase colonic epithelial tight junction permeability via a RhoA‐ROCK‐dependent pathway. FASEB J. 28, 1059–1070 (2014). www.fasebj.org